Intelligence, security and asymmetric warfare: strategies for solution - Singh, Dhirendra (New Delhi, 2010)
This book eminent defence analysts and security officials, discuss some of the current issues, the threat posed, emerging concepts covered in the fields of Intelligence, Security and Asymmetric Warfare and their reflections on India's security.
Keywords: National security